STUDI EVALUASI IMPLEMENTASI PERDA NOMOR 2 TAHUN 2011 TENTANG PENYELENGGARAAN PENANGGULANGAN BENCANA DI KABUPATEN PEMALANG - Pubita Sasti Fintani; Edi Santosa; Sulistyowati . (Journal of Politic and Government Studies, 2014)
The purpose of this study was to determine the evaluation of the implementation ofRegulation No. 2 of 2011 on the implementation of disaster management in all district.Variables are used to seeing the implementation of Regulation No. 2 of 2011 is acommunication variable, resources, disposition, and bureaucratic structures. To evaluate theimplementation using an indicator variable that consists of agenda-setting, policy formulation,adoption or legitimacy of the policy, and the policy assessment or evaluation. These indicatorsare then analyzed qualitatively descriptive phenomenon is happening. By looking at the variousaspects that have been analyzed can be concluded that the law No. 2 of 2011 on theimplementation of disaster management in the district have not been implemented properly andits implementation has not been effective.Keywords: Implementation, Effectiveness, Disaster